Process optimization and characterization of pectin derived from underexploited pineapple peel biowaste as a value-added product. (February 2022) - Shivamathi, Chellam Somasundarar; Gunaseelan, Sathaiah; Soosai, Michael Rahul; Vignesh, Nagamalai Sakthi; Varalakshmi, Perumal; Kumar, Rajaram Shyam; Karthikumar, Sankar; Kumar, R. Vinoth; Baskar, Rajoo; Rigby, Sean Patrick; Syed, Asad; Elgorban, Abdallah M.; et al.
Abstract: Biowastes generated from the food processing industries cause environmental issues due to nitrogen, phosphorous, macronutrients, and water contents. These nutrients make the wastes more susceptible to fermentation, thus causing pollution. However, these biowastes contain a high level of marketable bioproducts extracted for value-added products like pectin. The current study deals with the pectin extraction from pineapple peel (PP) waste employing the ultrasound-assisted extraction (UAE) technique. Further, response surface methodology (RSM) was employed to determine the optimum conditions for maximum pectin extraction using independent variables like ultrasonication time (15–30 min), liquid to solid (LS) ratio (10–20 mL/g), temperature (50–80 °C) and pH (1–2). A maximum pectin yield (16.24%) was attained at 15.20 mL/g of LS ratio, 21.88 min of ultrasonication, 70.83 °C and pH 1.0. The extracted pectin was purified using anion exchange chromatography (DEAE cellulose), and the purity index was 89.5–90%. The purified pectin fractions were analyzed through thin-layer chromatography and characterized by SEM, FT-IR, TGA, XRD, 1D and 2D NMR. The polysaccharide content was quantified using the phenol-sulfuric assay. Other functional properties like emulsification, oil and water holding capacity were also measured. In addition, based on antinutritional and antioxidant properties, the extracted PP pectin was confirmed to be a toxic-free compound. A detailed structural and physio-chemical properties study confirmed the pectin from PP was of good quality and could be utilized as a value-added product in the pharmaceutical industry. Graphical abstract: Image 1 Highlights: CCD-RSM was used to optimize for better yield of pectin from pineapple peel. High methoxylated pectin was extracted from pineapple peel using UAE. The purity index of purified pectin by DEAE cellulose was found to be 90%. The purified pectin has 74.64% of anhydrouronic acid. Purified pectin characterized and compared to commercial citrus pectin.